PSVII-9 Ruminal papillae morphology and volatile fatty acid profile of beef feedlot steers fed L. salivarius L28 in replacement for tylosin. (7th December 2018) - Hoffmann, C; Sarturi, J; Reis, B; Miller, M; Brashears, M; Millen, D; Milopoulos, J; Opheim, T
Abstract: The effects of replacing a known feed additive (tylosin) with a novel direct-fed microbial (L. salivarius L28) on ruminal papillae morphology and volatile fatty acid (VFA) profile of feedlot steers fed a steam-flaked corn-based diet were evaluated. Using a randomized complete block design, 144 single-sourced crossbred steers (BW = 371 ± 19 kg) were blocked by initial BW and randomly assigned to 1 of 3 treatments (12 pens/treatment; 4 steers/pen). Treatments consisted of: a) no feed additives [Control]; b) monensin (330 mg/animal-daily) and tylosin (88 mg/animal-daily) [MonTyl]; and c) monensin (330 mg/animal-daily) and L. salivarius L28 (107 CFU/animal-daily) [MonPro]. Animals were harvested in two groups (140 d; 158 d). Individual samples (6 cm2) of ruminal cranial sac epithelium were collected (n = 144), preserved under refrigeration (4oC), and immersed in 70% alcohol. Ruminal tissue was trimmed (2 cm2), in which papillae were counted, followed by random removal of 12 papillae specimens for further area electronic scanning (The University of Texas Health Science Center of San Antonio, Image Tool). During the first harvest group, individual samples (50 mL) of ruminal fluid (n = 53) were collected following evisceration (VFA analysis). Data were analyzed using the GLIMMIX procedures of SAS, using pen as experimental unit. Steers fed MonPro tended (P = 0.09) to increase number of ruminal papillae compared to Control, whereas steers fed MonTyl were intermediate. Combinations of feed additives did not affect papillae area, size, or absorptive area (P ≥ 0.26). Ruminal VFA profile was not affected (P ≥ 0.12) by dietary treatments. Ruminal absorption potential maybe positively affected by feeding MonPro during cattle finishing phase. Feed additives tended to affect ruminal physical components at a greater extension than momentary metabolical markers (ruminal VFA molar proportions). Long-term effects of feed additives on ruminal morphology needs to be further investigated.